Moralitas Dan Identitas LGBT Dalam Dinamika Sosial Kontemporer - Bintang Akhiruddin, Muhammad; Mulawarman, Mulawarman; Nur Wahyuni, Intan; Salsabila, Zalfaa; Agustimban, Sultan (Jurnal Ilmu Pemerintahan, 2025)
This research aims to conduct an in-depth analysis of the issues of morality and LGBT identity within contemporary social dynamics through a qualitative approach using literature study methods. Data were collected from a secondary source, namely, scientific journals. The analysis was conducted with a thematic approach to identify the main patterns in the developing perspectives within the relevant literature. The research results indicate that the construction of morality and LGBT identity is influenced by various social, cultural, and political factors, and undergoes transformation along with changes in social dynamics. This research contributes to understanding the complexity of LGBT issues in the context of morality and identity, and offers insights for the development of inclusive social policies and practices.